Reasons for the adoption of governance in Algerian banks (Journal of Economic Additions, 2019)
The Algerian banking system has undergone many reforms. Nevertheless, thebanking sector is still suffering from a number of shortcomings and negativeswhich limit the effectiveness of these reforms and turn them into achieving thedesired objectives. This requires the need to adopt and work towards governance inorder to improve the banking system And to qualify them for integration into theglobal economy.The most important resultsthat the need to apply the principles of governance inAlgerian banks did not arise from nothing, but the growing interest in this conceptis due to what he knew Algerian banking system of gaps, led him to exposure totremors that destabilized the stability and credibility of the banking system.Key words: Governance, Algerian banking system, gaps, stability.JEL Classification:G38,G24,G39,C62